On arranging dual-polarised antennas in 3D wave field synthesis - Kotterman, Wim A.Th; Schirmer, Christopher; Landmann, Markus; Del Galdo, Giovanni (8th European Conference on Antennas and Propagation, EuCAP 2014, 2014)
For three-dimensional electromagnetic wave field synthesis, the orientation of dual-polarised antenna elements has influence on the size or volume of the usable 'quiet zone' or 'sweet spot'. The customary choice of polarisation directions along phi and theta allows for the full angular range over which wave fields can be synthesised. But, we show that this choice effectively reduces the number of available active radiators in case a single polarised wave is to be synthesised, with direction of incidence near the phi-axis. One option to maintain synthesis quality is driving both types of polarised elements, meaning also adding channel emulators that are an appreciable cost factor. However, not all applications need fully 3-D incident fields and some simple compromises for specific applications are proposed.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Anechoic chamber; Antennas; Over-the-air; Wave field synthesis